The effects of mentorship and educational videos on nursing students’ physical examination skills: a clinical audit - Mohammad-Amin Nasiri; Mahdieh Sabery; Mahboubeh Rezaei; Hamidreza gilasi (BMC Nursing, 2023)
Abstract Background Poor competence in clinical examination skills among nurses has been reported in practice, and there is a strong consensus that physical examination (PE) education must be improved. However, deficiencies cannot be resolved by theoretical training alone, and new training approaches are required to enable nursing students to perform PE accurately. This study aimed to determine and compare the effect of two new educational methods (mentorship and educational video methods) on the physical examination skills of Iranian nursing students. Methods This study was a clinical audit with three group pretest posttest design. Eligible nursing students were recruited through the census method and assigned to three groups (mentorship, educational videos, and control group) using permuted block randomization. Students were taught PE skills in three vital systems through three approaches (mentors, educational videos, and routine educational methods). Data were collected using a two-part instrument consisting of a demographic information questionnaire and a 32-item checklist for assessing the students’ skills in examining the respiratory system (10 items), cardiovascular system (13 items), and 12 cranial nerves (9 items). Data were analyzed using SPSS software version 16 and descriptive and analytical statistical tests. Results At baseline, students in all groups scored less than half of the possible scores in all three systems, and the mean scores of the three groups were not statistically different (P > 0.05). After the intervention, the mean scores of students in the mentorship group increased significantly in all three systems (P < 0.001), whereas the mean scores of students in the educational video group and the control group did not change significantly (P > 0.05). Furthermore, after the intervention, the mean scores of the educational video group and the control group did not significantly differ in any of the three systems (P > 0.05). The ANCOVA showed that with posttest score as the covariate, PE skills in all three systems improved one week after the intervention in the mentor group compared to the control group and the educational video group. However, PE skills in all three systems did not improve one week after the intervention in the educational video group compared to the control group. Conclusions The mentorship method is more effective than the educational video and routine methods for teaching PE skills to nursing students. Nursing schools can use the mentor method in training nursing students, and it is recommended to revise the PE lesson unit in the nursing curriculum and exchange it from a purely theoretical-based unit to a mixture of theoretical and clinical-based training. Educational videos alone cannot improve nursing students’ PE skills; thus, if educational videos are used to teach clinical skills, it is necessary to hold hands-on sessions to provide feedback to students and correct their mistakes.